Venous thromboembolic events: case history - T.V. Shelkovnikova; Kh.P. Takhchidi; G.V. Vavin; N.Yu. Shishlyannikova (РМЖ "Клиническая офтальмология")
T.V. Shelkovnikova1, Ch.P. Takhchidi2, G.V. Vavin3, N.Yu. Shishlyannikova3 1Kemerovo Regional Clinical Hospital, Kemerovo, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Kemerovo State Medical University, Kemerovo, Russian Federation This article describes a 74-year-old woman with central retinal vein thrombosis after recurrent pulmonary embolism (PE). Genetic testing for mutations and hemostasis gene polymorphism as well as testing for antiphospholipid antibodies have clarified the recurrences of venous thromboses of various localization. Elevated levels of fibrinogen, soluble fibrin monomer complexes, factors V and VIII, von Willebrand factor, and intravascular platelet activation factor were revealed. The presence of two or more genetic markers of thrombophilia as well as antiphospholipid antibodies promote endotheliosis and thrombogenesis. Clinical manifestations of these phenomena are retinal hemorrhages with retinal ischemia and recurrent central retinal vein thrombosis and PE. More careful approach to treatment choice and prescription of prolonged anticoagulant therapy using direct inhibitors of Xa factor and low-molecular-weight heparin is required. Complex treatment for venous thromboembolism and  central retinal thrombosis (involving neuroprotective agents) should be applied. Keywords: hereditary thrombophilia, thromboembolism, pulmonary embolism, PE, retinal vein occlusion, hemostatic system. For citation: Shelkovnikova T.V., Takhchidi Ch.P., Vavin G.V., Shishlyannikova N.Yu. Venous thromboembolic events: case history. Russian Journal of Clinical Ophthalmology. 2019;19(4):246–250.